Global Well-Posedness in Set Optimization. (26th October 2021) - Miholca, Mihaela
Abstract: In this paper we introduce and study two concepts of global well-posedness for set optimization problems in Hausdorff topological vector spaces. Some relationships among these notions and generalized e -well-posedness concept already existent in the literature are established. Sufficient conditions are also given in order to guarantee global well-posedness. Our notions and results extend similar concepts and results established for set optimization problems in metric spaces.